2013
DOI: 10.1007/s00109-013-1045-x
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB in colorectal cancer

Abstract: Colorectal cancer (CRC) is a leading cause of morbidity and mortality worldwide, responsible for more than half a million deaths annually. CRC is a multistep process that entails the accumulation of genetic/epigenetic aberrations, which lead to the simultaneous failure of protective mechanisms and the activation of tumorigenic pathways. In most cases of CRC a deregulation of the Wnt-signaling pathway is required. The transcription factor nuclear factor κB (NF-κB) has been recognized as a key player in the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 69 publications
5
56
1
Order By: Relevance
“…A tumorigenic niche, composed of inflammatory cells, myofibroblasts, other cell types, and extracellular components, is essential for the maintenance of malignancies and facilitates tumor initiation, progression, and survival. Indeed, human colon cancer tissues are infiltrated by inflammatory cells and plasma levels of cytokines are often raised in CRC patients (Vaiopoulos et al 2013). Regulation of the inflammatory response is very complicated but many signaling pathways involve the transcription factor NFκB.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…A tumorigenic niche, composed of inflammatory cells, myofibroblasts, other cell types, and extracellular components, is essential for the maintenance of malignancies and facilitates tumor initiation, progression, and survival. Indeed, human colon cancer tissues are infiltrated by inflammatory cells and plasma levels of cytokines are often raised in CRC patients (Vaiopoulos et al 2013). Regulation of the inflammatory response is very complicated but many signaling pathways involve the transcription factor NFκB.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…In CRC, cross-talk occurs between NF-kB and many other important signaling pathways, such as the RAS, AKT, and WNT signaling pathways. Together, these pathways form a complex network that regulates the progression of CRC (15,19). Our preliminary work and a published microarray analysis showed that the downregulation of SAFB expression increased the activation of NF-kB signaling in CRC, but the molecular mechanisms by which SAFB regulates the activation of NF-kB signaling are unclear.…”
Section: Introductionmentioning
confidence: 76%
“…Recently, a connection between inflammation and carcinogenesis has been evidenced. NF-κB is a transcription factor, which regulates essential pathways involved in the initiation and propagation of colorectal cancer by controlling inflammation, the cell cycle, and cell survival (Vaiopoulos, Athanasoula, & Papavassiliou, 2013). Overexpression and constitutive activation of NF-κB have been observed in colorectal cancer, especially in colitis-associated colorectal cancer (Grivennikov et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The results of human clinical trials have further revealed that regular use of nonsteroidal antiinflammatory drugs is associated with a decrease of incidence and mortality of colorectal cancer (Algra & Rothwell, 2012;Flossmann & Rothwell, 2007). NF-κB signalling also controls the growth, angiogenesis, and metastasis of colorectal cancer (Vaiopoulos et al, 2013). In addition, NF-κB suppressed apoptosis by modulating XIAP, c-Jun, and reactive oxygen species (Weng, Feng, Qin, & Ma, 2014).…”
Section: Discussionmentioning
confidence: 99%